2014
DOI: 10.1126/science.1244908
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Soil Production and Weathering in the Southern Alps, New Zealand

Abstract: Evaluating conflicting theories about the influence of mountains on carbon dioxide cycling and climate requires understanding weathering fluxes from tectonically uplifting landscapes. The lack of soil production and weathering rate measurements in Earth's most rapidly uplifting mountains has made it difficult to determine whether weathering rates increase or decline in response to rapid erosion. Beryllium-10 concentrations in soils from the western Southern Alps, New Zealand, demonstrate that soil is produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
216
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(232 citation statements)
references
References 83 publications
15
216
0
1
Order By: Relevance
“…Several authors (Riebe et al 2004a, b;West et al 2005;Maurin et al 2005;Larsen et al 2014) showed the importance of physical erosion on denudation rates. Erosion can be calculated with the chemical depletion factor, CDF.…”
Section: Soil Production and Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors (Riebe et al 2004a, b;West et al 2005;Maurin et al 2005;Larsen et al 2014) showed the importance of physical erosion on denudation rates. Erosion can be calculated with the chemical depletion factor, CDF.…”
Section: Soil Production and Formationmentioning
confidence: 99%
“…Most soils feature a maximum possible CDF of 0.5 to 0.1 (that finally depends on climate and parent material: Dixon and von Blanckenburg 2012;Larsen et al 2014); consequently soil erosion accounts for at least half of the denudation.…”
Section: Soil Production and Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…On Mars, as on Earth, mechanical weathering is the precursor to sediment production and rock erosion, see, for example, refs 1-4, and can potentially influence chemical weathering and subsequent atmospheric feedbacks [5][6][7][8] . Hence, identifying the key drivers of weathering is therefore possibly tantamount to understanding the key drivers of landscape change on the Martian surface.…”
mentioning
confidence: 99%
“…Datasets from soil pits and riverine fluxes show a monotonic relationship between both the denudation rate and weathering rate in some cases (Millot et al, 2002;Dixon et al, 2009b;West et al, 2005), but also 30 evidence a possible maximum erosion rate above which the weathering rate decreases (Dixon and von Blanckenburg, 2012). Recent data from the Southern Alps in New Zealand have challenged the existence of this erosion rate limit by demonstrating that weathering was able to continue increasing at the highest erosion rates when rainfall is abundant (Larsen et al, 2014). In such regions, landslides constitute a significant weathering reservoir (Emberson et al, 2016a, b).…”
Section: Introductionmentioning
confidence: 99%